KONSEP TEOLOGI ISLAM DAN TASAWUF AKHLAKI, IRFANI DAN FALSAFI SERTA PENGEMBANGAN PEMIKIRANNYA - Maulana Muhammad, Salim, Mohammad Fadil (PRODI PAI FIK UNIRA MALANG, 2024)
As a part of the Islamic intellectual tradition, Sufism is a discipline that focuses on the study of true and complete knowledge of metaphysical realities, especially the reality of God. Although oriented toward metaphysical matters, it cannot be approached merely through rational thought, as is the case with philosophy. Sufism has an epistemological framework that differs from reason or intellect. Today, Sufism has become a fundamental need for modern humans, who, according to Seyyed H. Nasr, have experienced despair and are in need of hope. Sufism plays a significant role in realizing the noble aspirations of humans seeking a harmonious life between physical and spiritual needs. Additionally, Sufism has not only revitalized Islamic ethics over centuries, but it has also become a central instrument in contemporary times, directly contributing to the socio-political-economic aspects of Islamic society through their fraternal relationships (Sufi brotherhoods). Moreover, there are several important aspects related to theology, namely ethical Sufism and philosophical Sufism.